KUALITAS AIR BAWAH TANAH DI WILAYAH PESISIR KABUPATEN BADUNG. - Sundra, I Ketut (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 1 No 2)
This research was conducted for ground water analysis in beach area in Badung Regencyin Pebruary and May, 2006 at 6 experiment location i.e. ground water in Tanjung Benoa,Nusa Dua, Kuta, Legian, Canggu, and Peti Tenget with purposive sampling method. Dataof those sites which were collected in situ as well as the output of the laboratories for 6experiment place during the rainy and dry seasons showed that 6 (TDS, nitrite, hardness,phosphate, BOD and COD) out of 20 parameters in those sites exceeded the standards forfirst grade of water (Kepmen LH No. 82 tahun 2001). Based on water quality status,Tanjung Benoa, Nusa Dua and Legian ground water show that bad dirty water. whileKuta, Canggu, and Peti Tenget ground water show that medium dirty water. It can beconcluded that water quality on these ground water in 6 ground water in coastal area inBadung Regency has not met the best water quality for drinking water.
Keywords: ground water, waste, water quality, water quality status.